PROFILE OF SUICIDE CASES IN A PENITENTIARY IN THE PERNAMBUCO HINTERLAND - Alencar, Alecrides Marques; Pacheco, Alessandra Gomes Marques; de Souza, Beatriz Medrado; Pacheco, Edson Jorge (Seven Editora, 2025)
The research seeks to present the profile of suicide cases in a penitentiary in the hinterland of Pernambuco. For this, it was necessary to understand triggering factors of suicide; to identify precipitating factors for the commission of suicide and to propose protective factors for the development of a suicide prevention policy. The research addressed legal aspects related to penal execution, contextualizing suicide in the prison environment, through the proposal of a qualitative, exploratory and descriptive cross-sectional methodology, with the survey of information on completed suicides recorded in a prison settlement, from 2007 to 2019, based on documentary analysis, with quantification and tabulation procedures as a form of data systematization. As the main result of the study based on the profile, 07 cases were found, and it was observed that in most of the events (4 cases), the individuals had arrived at the prison by recent transfer from another distant unit, located in the same state.DOI: https://doi.org/10.56238/sevened2024.037-210